Solve the equation.

y + 6 = –3y + 26

y = –8

y = –5

y = 5

y = 8

y + 6 = –3y + 26

y = –8

y = –5

y = 5

y = 8

y + 6 = –3y + 26

y = –8

y = –5

y = 5

y = 8

Asked
6 months ago

Viewed
974438 times

**Answer:**

y=5

**Step-by-step explanation:**

**Answer:**

C

**Step-by-step explanation:**

EDGE

Solve for e

Enter your username or email to reset your password. You will receive an email with instructions on how to reset your password. If you are experiencing problems resetting your password contact us or send us an email